AN INVESTIGATION ON DAMAGE OF AEOLESTHES SARTA SOLSKY ON INDUSTRIAL TIMBER IN IRAN - Ebrahim Farashiani (Regional Information Center for Science and Technology (RICeST), 2002)
Sart long horn beetle (Aeolesthes sarta) is one of the most important pests of elm, walnut, poplar, sycamore and... in Iran. The wood of these trees is valuable and they can be attacked by A. sarta. For the first time in the world, during 1997 -2001, quality and quantity of damage of A. sarta on host trees was investigated. To evaluate damage amount and reduction of wood production, the number and volume per cubic meter of galleries, and quantity of wood fed by the larvae were evaluated.Also for evaluation of quality damage, nonaffected wood as well as infected wood were compared in terms of economical and industrial values. The results indicated that the quantity damage on the wood of trees was considered as high and larvae fed about 20% of wood. In the mean time, because of dying of the trees, production of wood stopped completely.Sometimes, heartwood particularly pith of the trees was fed and about 50% Of trunk become hollow. Because of damages and existence of numerous galleries, the quality of wood has lowered and so wood has no industrial use and some of tree:species such as walnut and alder lost their economical value up to 90%.